Analisis Debit Maksimum Pada Long Storage Sungai Serua Di Lingkungan Universitas Pembangunan Jaya - Jesika Ignes; Rizka Arbaningrum (Jurnal Proyek Teknik Sipil, 2021)
Flood disasters are not entirely caused by natural factors but can also be caused by human behavior. So an effort is needed for flood control, one of which is by making a storage pool or by another name is long storage. The storage pool is expected to accommodate runoff discharge and reduce flooding. This flood control effort is also applied to the Serua River in the Development Pembangunan Jaya University. So with the long storage design that stretches across the Serua River, it is hoped that it can temporarily accommodate the flow of flowing water. This study aims to analyze the maximum discharge that occurs in the long storage of the Serua River, especially in the Development Pembangunan Jaya University on the 20 years, 50 years, and 100 years return period by modeling using the HEC-RAS application. The output of the HEC-RAS application shows that the Serua River cross section at the 20-year return period is able to accommodate the planned flood discharge, but at the 50-year and 100-year return periods there is a cross-section that is unable to accommodate the planned flood discharge because the flood elevation is above the embankment elevation, so it can cause flooding.